2005
DOI: 10.1007/s00221-005-2240-y
|View full text |Cite
|
Sign up to set email alerts
|

Decreased anxiety levels related to aging

Abstract: The present experiment investigated the effects of aging on emotional behavior, without concomitant influences from any previous behavioral manipulation apart from weighing the rats. Anxiety-related behaviors were measured in the elevated plus-maze (EPM). Performance in the open field (OF) was also assessed to control for any effect of aging on exploratory behavior that could account for changes in emotional behavior. Fifty-two naïve male Wistar rats of 3 (3MO), 17 (17MO), or 24 (24MO) months, were submitted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 37 publications
4
19
4
Order By: Relevance
“…Similar findings have been made in experimental studies showing greater reduction in motor activity [16] and diminished performance in skilled and unskilled motor tasks in aged rats [17,28]. Sustained high levels of glucocorticoids may compromise the ability to overcome ischemia-induced deficits both on the neuronal and functional level [18][19][20][21][22].…”
Section: Introductionsupporting
confidence: 74%
“…Similar findings have been made in experimental studies showing greater reduction in motor activity [16] and diminished performance in skilled and unskilled motor tasks in aged rats [17,28]. Sustained high levels of glucocorticoids may compromise the ability to overcome ischemia-induced deficits both on the neuronal and functional level [18][19][20][21][22].…”
Section: Introductionsupporting
confidence: 74%
“…While these results differ from those of some experiments which report that rats normally avoid the open arms of the maze (Andrade et al, 2003;Baguszewski and Zagrodzka, 2002;Torras-Garcia et al, 2004), other investigators (Imhof et al, 1993) have also reported that their younger rats spent more time in the open arms of the maze than in the closed arms. As the age of the rats increases, there are corresponding increases in the preference for the closed arms of the maze, which would indicate an increase in baseline anxiety levels.…”
Section: Discussioncontrasting
confidence: 67%
“…There were several reasons for this: firstly, older animals better correspond to the clinical situation of LID in patients with PD. Secondly, previous studies have reported that older rats display a significantly lower basal anxiety level than younger animals (Boguszewski and Zagrodzka 2002;Torras-Garcia et al 2005), which ensured that sufficient animals had a low anxiety state. Thirdly, older rats have stable weight and, as rats are prandial drinkers and citalopram was administered via drinking water in the present study, it ensured that all rats received equivalent doses.…”
Section: Discussionmentioning
confidence: 98%